Melaka network overcurrent protection & coordination analysis using PSCAD software - Hairi, Mohd Hendra; Kamarudin, Muhammad Nizam; Roslee, Fairoz; Mohd Isira, Ahmad Sadhiqin; Mohamed, Mohamed Fauzi Packeer (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
This paper presents a study on the modeling of the 132/33/11kV PMU Pulau Gadong network and the Melaka radial distribution feeder. The study proposes a protection scheme by providing the appropriate relay Pickup current/Plug Setting (PS) and Time Multiplier Setting (TMS )/Time Dial Setting (TDS) for the discrimination process and evaluating the effect of parallel transformers during faults. For this study, the IEC std 255-3 standard inverse IDMT curve characteristic was chosen for the simulation using the Power System Computer Aided Design (PSCAD). The results show that these values were trustworthy, which provide adequate and reliable protection for the whole network.